Effect of Rumen Undegraded Protein Level on Nutrient Digestibility and Rumen Fermentation Parameters of Dairy Cow - Widyobroto B. P.; S. P. S. Budhi; A. Agus; B. Santosa (Buletin Peternakan, 2002)
Artikel dalam bentuk PDF